Closing the Opportunity Gap: Identity-Conscious Strategies for Retention and Student Success: Edited by Vijay Pendakur, 2016. Sterling, VA: Stylus Publishing, 172 pages. ISBN: 978-1-620-36312-6, Paper, 29.95. Issue 3 (2nd July 2016) - Eberhardt, David
Abstract: Vijay Pendakur and his colleagues argue that higher education has largely failed underrepresented students by ignoring the particular challenges and needs associated with students' diverse identities in their academic success and persistence programs. They call for an intersectional approach that builds these programs with identity consciousness, and they share numerous examples for how institutions can establish them. Faculty, student affairs professionals, institutional leaders, and policy makers with interest in these issues will find both thoughtful, stimulating material and beneficial practical guidance within this work.